Identifikasi Proses Produksi Karpet Mobil untuk Meminimumkan Pemborosan (Waste) Menggunakan Pendekatan Lean Manufacturing - Santoso, Afiyah Febriana; Mundari, Siti (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Waste is an element that must be minimized in order to improve efficiency. This study aims to identify and minimize waste in the automotive mat production process at PT XYZ using a lean manufacturing approach. The main issues identified include high delays between processes, inefficient operator movements, suboptimal material flow. Through field observations, value stream mapping (VSM) analysis, and root cause analysis (RCA) using the 5 Whys method, the primary causes of waste were found to be a non-linear factory layout, accumulation of work in process (WIP), and suboptimal coordination and standardization between workstations. Proposed improvements include the implementation of 5S principles to organize the workspace and reduce buildup, optimization of material flow using floor markings and strategic buffers, as well as production line balancing and the adoption of a pull production system. These improvements are expected to enhance efficiency, reduce waste, and create a leaner and more competitive production process at PT XYZ.